Factors influencing intravenous methylprednisolone pulse therapy in Chinese patients with isolated optic neuritis associated with AQP4 antibody-seropositive neuromyelitis optica - Sitong Guo (Nature Portfolio, 2021)
Abstract This study investigated the factors influencing intravenous methylprednisolone pulse (IVMP) therapy for recovering visual acuity in Chinese patients with aquaporin-4 (AQP4) antibody-seropositive neuromyelitis optica-related optic neuritis (NMO-ON). This retrospective case series included 243 affected eyes of 182 patients (36 male, 146 female) diagnosed with NMO-ON in the Neuro-Ophthalmology Clinic of Beijing Tongren Hospital from September 2012 to September 2020. All patients with AQP4-antibody seropositivity had clinical manifestations of acute ON, excluding other diagnoses and received IVMP treatment at 500 mg/day or 1000 mg/day for 3 days. Primary outcome was the extent of improvement in logMAR visual acuity after IVMP treatment. The therapeutic influences of sex, age, baseline visual acuity, therapeutic intervals, and IVMP dose on acute NMO-ON were analysed. Chi-square tests, Mann–Whitney U-tests, Kruskal–Wallis tests, Spearman’s correlation coefficients, and multiple linear regression were used for statistical analysis. Age ranged between 7 and 80 years (median age, 44; interquartile range [IQR], 29–52) years. Among the 243 eyes, the median improvement in logMAR visual acuity was 0.3 (IQR, 0–0.9). Therapeutic efficacy of IVMP was significantly higher in female than in male patients (Z = 2.117, P = 0.034). The treatment effect gradually decreased with increase in age at onset (Rs = 0.157, P = 0.015), and visual improvement was significantly lower in patients aged > 50 years than in those ≤ 50 years (Z = 2.571, P = 0.010). When patients had low visual acuity at onset, improvements were more obvious (rho =  − 0.317, P < 0.001); however, final visual acuity was still low (rho = 0.688, P < 0.001). Therapeutic effect was negatively correlated with therapeutic intervals (rho = 0.228, P = 0.001). Dosage of methylprednisolone (1000 mg/day or 500 mg/day) did not significantly influence treatment efficacy (Z = 0.951 P = 0.342). Therefore, IVMP therapy can improve visual acuity in the affected eyes of patients with AQP4 antibody-seropositive NMO-ON with similar effect at 500 mg/day and 1000 mg/day doses. Sex, age at onset, and therapeutic intervals may influence the efficacy of IVMP in patients with NMO-ON.